Rad5 participates in lesion bypass through its Rev1-binding and ubiquitin ligase domains, but not through its helicase function - Masłowska, Katarzyna H.; Pagès, Vincent (Frontiers in Molecular Biosciences, 2022)
DNA Damage Tolerance (DDT) functions to bypass replication-blocking lesions and is divided into two distinct pathways: error-prone Translesion Synthesis (TLS) and error-free Damage Avoidance (DA). Rad5 is a a multifunctional protein that is involved in these DDT processes. Saccharomyces cerevisiae Rad5 contains three well defined domains: a RING domain that promotes PCNA polyubiquitination, a ssDNA-dependent ATPase/helicase domain, and a Rev1-binding domain. Both the RING domain and the ATPase/helicase domain are conserved in human Rad5 ortholog HLTF. In this study we used domain-specific mutants to address the contribution of each of the Rad5 domains to the lesion tolerance. We demonstrate that the two critical functions of Rad5 during DNA damage tolerance are the activation of template switching through polyubiquitination of PCNA and the recruitment of TLS, and that loss of one of those functions can be compensated by increased usage of the other. We also show that, unlike previously suggested, the helicase activity does not play any role in lesion tolerance.